2021
DOI: 10.52547/payesh.20.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Estimating willingness to pay for the Covid-19 vaccine using the conditional valuation method

Abstract: Objective: Conditional valuation method is one of the methods of estimating the willingness to pay and is a cost-benefit analysis. The aim of the present study was to estimate the average willingness of individuals to pay for the Covid-19 vaccine with a one-year and long-term protection period and to assess its contributing factors. Methods: The present study was a descriptive research. The required data were collected from 370 two-dimensional online questionnaires at the end of November 2020 from Iranians. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Signi cant differences in willingness to pay (WTP) for vaccines were observed across different levels of vaccine attitudes, indicating that respondents' attitudes, knowledge, and awareness were important factors in determining WTP. These ndings are consistent with previous studies by Nam Juan et al (2021) andAdeli et al (2021)…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Signi cant differences in willingness to pay (WTP) for vaccines were observed across different levels of vaccine attitudes, indicating that respondents' attitudes, knowledge, and awareness were important factors in determining WTP. These ndings are consistent with previous studies by Nam Juan et al (2021) andAdeli et al (2021)…”
supporting
confidence: 94%
“…The study found that participants were willing to pay an average of $ (9,11). The study examined several vaccines, including domestic, AstraZeneca, Sinopharm, and Sputnik, and found that gender did not have a signi cant effect on willingness to pay (WTP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, identifying the determinants associated with the WTP for the COVID-19 vaccine is essential for the government and other organizations to design an excellent intervention to be used in key populations [6][7][8][9]. Studies have evaluated the acceptance and the WTP for the COVID-19 vaccine globally but in Iran such evidence is limited [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…While the Iran Ministry of Health has initiated a vaccine dissemination process among HCWs to control the pandemic, surveys show that many of these employees are unwilling to receive their vaccine. [ 9 ] Therefore, it is extremely important to understand the intentions, motivations, and barriers affecting HCWs decision to get vaccinated against COVID-19. This knowledge can help policymakers to develop effective interventional programs to increase COVID-19 vaccination acceptance among HCWs.…”
Section: Introductionmentioning
confidence: 99%